The quality of business communication depending on emotional dispositions and personality traits - Nikić, Gordana; Mitrović, Milena; Travica, Vesna (Industrija, 2014)
The main goal of this paper is to examine connection between attachment styles, emotional intelligence, life satisfaction, personality traits and humour styles with employed people, as well as to discuss implications of this connection on the quality of business communications. The survey includes 240 participants from Serbia. The structure of the convenience sample is heterogeneous and it includes employees and managers of both sexes and of a various age. The instruments used are: Emotional skills and competence questionnaire (Takšić, Moharić, Munjas, 2006), Experiences in Close Relations (Kamenov & Jelić, 2003), Personality Questionnaire (Zuckerman, 2002), Humour styles Questionare (Martin et al, 2003) and Satisfaction With Life Scale (Diener, 1985) . The results indicate to the existence of significant positive correlation between secure attachment style, affiliative and self-enhancing humour style, activity, sociability and life satisfaction. There is also a positive correlations between preoccupied attachment style and self- defeating humour style, and a moderate negative correlation between preoccupied attachment style, self- enhancing and aggressive style of humour, activity, sociability as well as the overall life satisfaction.